The use of an Accesory Medial Portal in Anatomic ACL Reconstruction a Prospective Ct- Study - Chouliaras, Vasileios Theodore (Orthop J Sports Med, 2014)
OBJECTIVES: The purpose of this study was to evaluate if any differences exist regarding the position and the length of the femoral tunnel between the anterior cruciate ligament (ACL) reconstruction (ACLR) with the use of an accessory medial portal and the ACLR with no use of accessory medial portal using computed tomography (CT) imaging. METHODS: Twenty-five consecutive patients that underwent ACLR with the aid of an accessory medial portal (Group A) and 25 ACL-reconstructed (ACL-R) patients with no use of the accessory medial portal (Group B) formed the two study groups. The femoral tunnel angle (FTA) was measured on CT and the femoral tunnel length (FTL) was measured intraoperatively. Unpaired t-tests were used to examine differences regarding FTA and FTL between the two groups. The level of significance was set at α=0.05. RESULTS: Mean group values (range, standard deviation) for FTA were 33.9º (30º - 41º, 2.9º) and 48.2º (43º - 59º, 4.4 º) and for FTL 36.2mm (30-39, 2.4) and 44.2mm (39-48, 3) for groups A and B respectively (p<0.005). CONCLUSION: With the use of an accessory medial portal the femoral tunnel is placed in a more oblique position in coronal plane as compared to the conventional AM portal technique, closer to the real anatomical position of the posterolateral bundle. Additionally the femoral tunnel length with this new technique is shorter than this with the AM portal but long enough for using the smaller button which has been proposed to reduce the motion of the graft within the tunnel.